Ocular allergy - Khathutshelo P. Mashige (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2017)
Aim: To systematically review relevant literature investigating the classification and nomenclature, epidemiology and pathophysiological mechanisms, as well as diagnosis and treatment of ocular allergy. Method: The Medline, PubMed, Elsevier Science Direct, and Google Scholar databases were used to search for evidence-based literature on ocular allergy.Main outcome measures: Classification and nomenclature, epidemiology and pathophysiological mechanisms, diagnosis and management of ocular allergy.